Fuzzy Keyword Search with Safe Index over Encrypted Cloud Computing - Lixi Liu; Chi Zhang; Shaowen Yao; Shipu Wang; Wei Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As cloud computing becomes more and more utilized, sensitive data are being stored in cloud central servers. To ensure privacy, these data are usually encrypted before uploading, which makes searching complicated. In this paper we propose architecture of fuzzy keyword search with safe index. Bloom filter is used to build safe index which increases the searching effectiveness on a large dataset. The size of index is fixed so that the space efficiency is promoted. The experiment result shows that our searching scheme is effective and can be adapted to large encrypted file system.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3419